Optimum Sustainable Design Approach of a Granular Pile Anchor System in Mitigating Shallow Foundation Failures on Expansive Clay - Siang, Alvin John Lim Meng; Ehab Hamad Sfoog,; Sim Sy Yi,; Nickholas Anting Anak Guntor,; Faisal bin Sheikh Khalid,; Mohd Hidayat Rabon, (International Journal of Integrated Engineering, 2024)
Expansive soil is known for its capacity to undergo substantial volume fluctuations, expanding upon water absorption, and contracting during the drying process thus having profound problems for infrastructures, specifically for shallow foundations, which then requires periodic maintenance and repair works. This ultimately highlights the importance of a sustainable design approach to avoid unwanted consequences. Therefore, this research will be the forefront in addressing this issue by utilizing granular pile anchors (GPA) with various design alternatives to mitigate the heaving and swelling forces induced by expansive soil. This is achieved through numerical modelling analysis using the advanced 3D finite element software, PLAXIS which is focused in examining an optimal foundation structure design of GPA aimed at mitigating heave. The results showed that with the addition of GPA, there was a potential reduction of heave and to the uplift force on the foundation structure. The magnitude of the improvements was found to be controlled by three main independent design parameters of GPA which are the ratio of the GPA length to its diameter (L/D), the ratio of GPA length to the expansive soil layer thickness (L/H), and the area replacement ratio (Ar) which is the ratio of the foundation footing area to GPA cross section area. The largest improvement encountered compared to unreinforced shallow foundation was found to be using a design parameter of L/H = 2 and Ar = 4.0 where there was a 91.5% and 96.99% reduction in heave and uplift pressure respectively. Therefore, a shallow foundation can be constructed with the addition of GPA incorporating the optimum design parameters to maximise stability.